食事に関係なく投与され得る急速な開始および延長された痛覚消失のためのヒドロコドンおよびアセトアミノフェンを含む延長放出組成物 (2016)
本開示は、痛覚消失の急速な開始、および投薬間隔の終わり近くでのアセトアミノフェンのレベルの低減をもたらす、ヒドロコドンおよびアセトアミノフェンを含む延長放出医薬組成物を提供する。また提供するのは、アセトアミノフェン含有組成物を用いて処置される対象において、アセトアミノフェン誘発性肝傷害のリスクを低減するための方法、ならびにそれを必要とする対象において疼痛を処置するための方法である。本組成物は、対象に経口投与されたとき、組成物の投与の約０．７５時間後から約１０時間後まで、少なくとも約５ｎｇ／ｍＬのヒドロコドンの処置血漿中濃度を維持する。 The present disclosure provides an extended release pharmaceutical composition comprising hydrocodone and acetaminophen that provides a rapid onset of analgesia, and reduced levels of acetaminophen near the end of the dosing interval. Also provided are methods for reducing the risk of acetaminophen-induced hepatic damage in a subject being treated with an acetaminophen containing composition, as well as methods for treating pain in a subject in need thereof.